PENGARUH PEMBERDAYAAN DAN PEMBINAAN TERHADAP KOMITMEN ORGANISASIONAL DI PT. BANK SUMUT TBK. CABANG MEDAN - Indra, Aulia (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2020)
PT Bank SUMUT Tbk. Medan is one of the regional-owned enterprises that certainly requires skilled and deft labor in providing services to the community. As a banking company, the company also indirectly strives to improve its performance. This is inseparable from efforts to improve maximum service to the community as service users. This recent phenomenon is where the performance of PT Bank SUMUT Tbk. Medan experienced a decline, this was due to the existence of plans that had been arranged to attend the workshop canceled and replaced with other activities. This has an impact on employees' commitment to the company. The purpose of this study was to analyze whether empowerment and coaching effect organizational commitment at PT Bank SUMUT Tbk. Medan. The sample in this study amounted to 93 people with the analysis technique used is multiple linear regression. The results showed that coaching and empowerment had a significant and partial effect on organizational commitment. Organizational commitment variable (y) is influenced by variable variable X1 (empowerment) and X2 (coaching) together by 25.2% and the remaining 74.8% is determined by other variables outside the contribution of this study.